Seletividade e eficiência de herbicidas usados no controle de plantas daninhas infestantes do sorgo sacarino - Fernandes, Franciele Fátima (2016)
The scarcity of herbicides registered for weed control in sweet sorghum is one of the major challenges faced by growers. The aim of this work was to evaluate the selectivity of herbicides to sweet sorghum crop. The statistical design used was the completely randomized blocks, arranged in a scheme 3 x 10, with four replications. In fator A, the genotypes of sweet sorghum (BRS 509, BRS 506 e BRS 511) were allocated and in B, the combinations of herbicides (atrazine + s-metolachlor – 1,665.0 + 1,035.0; tembotrione – 100.8; atrazine – 1,500.0; flumioxazin – 50.0; flumioxazin + tembotrione – 50.0 + 100.8; atrazine+ s-metolachlor + tembotrione – 1,665.0 + 1,035.0 + 100.8; atrazine + tembotrione – 1,500.0 + 100.8 e s-metolachlor – 1,440.0 g ha-1 of active ingredient), sprayed in pre and/or post- emergence of the crop. At 35 days after herbicides application, the visual symptoms of phytotoxicity in the crop and efficiency of weed control were evaluated. Height, stalk diameter, plant stand and weight of total green mass were evaluated in the moment of harvest, at 120 days after emergence (DAE). All treatments that had tembotrione caused severe symptoms of phytotoxicity to the sorgum cultivars BRS 506, BRS 509 e BRS 511, so, the application of the combinations cointaing tembotrione is not recommended. S-metolachlor presented high phytotoxicity to cultivars BRS 506 and BRS 511, and low to the cultivar BRS 509. The herbicides tembotrione, flumioxazin+tembotrione, atrazine+s-metolachlor+tembotrione, atrazine+tembotrione presented high control over Indivisa indivisa, Digitaria ciliaris and Urochloa plantaginea, so they can be recommended to these weeds management. Regarding the yield components of sweet sorghum, the herbicide with the highest selectivity, in general, was atrazine.